(untitled) (Journal of the Bangladesh Agricultural University, 2025)
This study investigates the feasibility of incorporating guava leaves powder into biscuits and cakes to enhance their nutritional value and evaluate their physical, chemical, and sensory properties. Biscuits and cakes were prepared with guava leaves powder at 0% (control), 2%, 4%, and 6% levels, substituting wheat flour. Results showed that as the incorporation level of guava leaves powder increased, the moisture content (2.1–3.0% in biscuits, 23.4–30.7% in cakes), protein content (6.74–6.91% in biscuits, 6.0–7.0% in cakes), and ash content (0.76–0.91% in biscuits, 1.1–1.3% in cakes) significantly increased, while carbohydrate and fat content decreased in both products. Physical properties, such as spread ratio of biscuit and specific volume of cake, decreased with higher level of incorporation. Among all formulations, the sample with 2% incorporation showed optimal functional properties, achieving the highest biscuit spread ratio (6.02) and cake specific volume (1.971 cm³/g). Sensory evaluation by a 10- member panel revealed that biscuits and cakes with 2% guava leaves powder received the highest overall acceptability scores (7.4 for biscuits and 6.7 for cakes on a 9-point hedonic scale), with significantly lower scores observed at 4% and 6% incorporation levels due to unfavorable changes in texture and flavor. These findings highlight guava leaves powder as a promising functional ingredient for bakery products where 2% incorporation provides the best balance of nutritional enhancement and consumer acceptability. J Bangladesh Agril Univ 23(3): 425–430, 2025